Faktor Lingkungan dan Perilaku yang Berhubungan dengan Kejadian Stunting pada Siswa SD di Wilayah Pertanian (Penelitian di Kecamatan Bulakamba Kabupaten Brebes) - Rudi Pangarsaning Utami; Suhartono Suhartono; Nurjazuli Nurjazuli; Apoina Kartini; Rasipin Rasipin (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : Stunting is identified by comparing measurements of childrent’s heights to the NCHS WHO2005growth reference population : children who fall potential as a result of suboptimal health and/or nutritionalconditions. Stunting prevalence in Indonesia still high level, this indicated health problem because associatedwith increase in morbidity and mortality, low cognitive capability and improper physical function.The purpose inthis study was to determine many environmental factors and behaviour associated with incidence of stunting.Methods : It was an observational research with case-control study design.Subject were divided into two groups: case and control groups in Elementary School student class 4 and 5 with 37 subject in case group and 53 subjectin the control group. Variables examined in this study was a history of exposure to pesticides, history of cigarettesmoke exposure, mosquito smoke exposure history, a history of using plastic as a place to store food is still hot,urinaryexcretioniodine (UEI), levels of urinary thyocyanate, anemia, TSH levels, Cholinesterase levels and BodyMass Index.Data was collected by interviewing, observation and measurement. Data would be analyzed using independent t–test or Mann Withney), bivariate analisys using Chi-Square and multivariate analysis using logistic regression.Result :This study indicated that the incidence of stunting was 37 %; 56,8% of them had history of pesticidesexposure. The results of the bivariate analysis showed that the risk factor of stunting in student is a history ofpesticides exposure with Odds Ratio (OR) 2,625. The result of logistic regression test showed there was asignificant association between the incidence of stunting with a history of pesticide exposure(OR 2,39).Conclusion :The history of pesticides exposure was the risk factor for stunting.Key words : Environmental and behaviour factors, stuting, elementary student, agriculture areas.